2013
DOI: 10.4028/www.scientific.net/amr.685.30
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of B<sub>4</sub>C Additions on Mechanical Properties of Fe-Cu-Co Matrix Composites for Diamond Tools

Abstract: The effects of boron carbide (B4C) additions on characteristic of diamond impregnated Fe-Co-Cu matrix composites have been investigated using powder metallurgy (PM) method. For this purpose, samples of Fe-(30-60)wt. % Cu–20 wt. %Co alloys and1wt. % B4C additions of its matrix were processed by cold pressing at 350 MPa, followed by sintering at 1100°C. Microstructural examination, hardness and wear tests were performed.The microstructure of Fe–Cu–Co alloys was very sensitive to the Cu content and pore closure t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…4 Boron carbide (B 4 C) has been used as a reinforcing element in many ferrous or non-ferrous metal matrix composites due to its high chemical and thermal stability, low density and higher hardness than many ceramics. [5][6][7][8] Simsir et al 5 produced B 4 C reinforced Fe-Co alloy matrix composites by hot press and showed that the wear resistance of the composite significantly increased with the addition of B 4 C. Oksuz et al 6 reported that the hardness of the Fe-Co-Cu 1 alloy increased by 44% with the addition of 1% B 4 C. In a study by Xibao, 7 it was reported that Fe/B 4 C composite coating can be applied successfully by plasma arc transfer (PTA) method. Ettefagh Far and Davoodi 9 produced the steel matrix B 4 C reinforced composite structure by gas tungsten arc welding method and investigated its corrosion resistance.…”
Section: Introductionmentioning
confidence: 99%
“…4 Boron carbide (B 4 C) has been used as a reinforcing element in many ferrous or non-ferrous metal matrix composites due to its high chemical and thermal stability, low density and higher hardness than many ceramics. [5][6][7][8] Simsir et al 5 produced B 4 C reinforced Fe-Co alloy matrix composites by hot press and showed that the wear resistance of the composite significantly increased with the addition of B 4 C. Oksuz et al 6 reported that the hardness of the Fe-Co-Cu 1 alloy increased by 44% with the addition of 1% B 4 C. In a study by Xibao, 7 it was reported that Fe/B 4 C composite coating can be applied successfully by plasma arc transfer (PTA) method. Ettefagh Far and Davoodi 9 produced the steel matrix B 4 C reinforced composite structure by gas tungsten arc welding method and investigated its corrosion resistance.…”
Section: Introductionmentioning
confidence: 99%